Institutional factors governing the deployment of remote experiments: lessons from the rexnet project - Hine, Nick (2014)
Remote labs offer many unique advantages to students as they provide opportunities to access experiments and learning scenarios that would be otherwise unavailable. At the same time, however, these opportunities introduce real challenges to the institutions hosting the remote labs. This paper draws on the experiences of the REXNET project consortium to expose a number of these issues as a means of furthering the debate on the value of remote labs and the best practices in deploying them. The paper presents a brief outline of the various types of remote lab scenarios that might be deployed. It then describes the key human and technological actors that have an interest in or are intrinsic to a remote lab instance, with a description of the role of each actor and their interest. Some relationships between these various actors are then discussed with some factors that might influence those relationships. Finally some general issues are briefly described.